2018
DOI: 10.18378/rvads.v13i1.4917
|View full text |Cite
|
Sign up to set email alerts
|

Atividade tóxica in vitro de Croton heliotropiifolius Kunth (Euphorbiaceae)

Abstract: Frequentemente encontrado na caatinga, brejo, restinga e cerrado brasileiro, o velame, Croton heliotropiifolius Kunth é popularmente conhecido por suas propriedades medicinais utilizada na dor de estômago, mal estar gástrico, vômitos, diarréia com sangue e para baixar a febre. Além das propriedades farmacológicas, seu óleo essencial apresenta atividade larvicida contra Aedes aegypti, assim como o extrato etanólico apresentou atividade inseticida considerável contra Sitophilus zeamais. O presente trabalho teve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Croton heliotropiifolius has medicinal properties. Velame is widely used by local communities in Brazil, especially for the treatment of gastrointestinal disorders and general infections involving fever (Brito et al ; Silva et al ). Consistent with our results, Araújo et al () reported the antimicrobial activity of C. heliotropiifolius against S. aureus and stated that EO has potential applications against multidrug‐resistant strains of Staphylococcus spp.…”
Section: Resultsmentioning
confidence: 99%
“…Croton heliotropiifolius has medicinal properties. Velame is widely used by local communities in Brazil, especially for the treatment of gastrointestinal disorders and general infections involving fever (Brito et al ; Silva et al ). Consistent with our results, Araújo et al () reported the antimicrobial activity of C. heliotropiifolius against S. aureus and stated that EO has potential applications against multidrug‐resistant strains of Staphylococcus spp.…”
Section: Resultsmentioning
confidence: 99%
“…The toxicity of several secondary metabolites, present in vegetal have been described (Silva et al, 2012). The methanol extract of C. heliotropiifolius showed moderate toxicity to the micro crustacean Artemia salina (Silva et al, 2018). After the end of the toxicological assays, it was verified that the EECroton showed to have some action on the central nervous system and peripheral action in the preestablished doses.…”
Section: Discussionmentioning
confidence: 98%
“…The essential oil has been described as larvicidal against Aedes aegypti (Doria et al, 2010). The methanolic extract of C. heliotropiifolius showed moderate toxicity against the microcrustacean Artemia salina and a low to medium percentage of cell growth inhibition on tumor lines tested (Silva et al, 2018(Silva et al, , 2017. The Human Toxicity Potential (HTP) is an important test to be performed early in the study of medicinal herb.…”
Section: Introductionmentioning
confidence: 99%